FACTORS AFFECTING THE EFFECTIVENESS OF TOURISM PROMOTION IN KWALA SERAPUH VILLAGE, LANGKAT - Ritonga, Husni Muharram; Sanny, Annisa; Rizky, M. Chaerul; Sihombing, Ayu Juni (Proceeding International Seminar of Islamic Studies, 2024)
Tourism promotion is one of the important activities to increase tourist visits to a tourist destination. The effectiveness of tourism promotion can be measured by looking at the increase in the number of tourists visiting these tourist destinations. This study aims to analyze the factors that affect the effectiveness of tourism promotion in Kwala Serapuh Village, Langkat. This research uses quantitative methods with a survey approach. The study population was tourists visiting Kwala Serapuh village, Langkat. The study sample amounted to 100 people taken by simple random sampling method. The research data were collected using questionnaires. Data analysis was performed using multiple linear regression analysis. The quality of promotion is the most influential factor on the effectiveness of tourism promotion in Kwala Serapuh village, Langkat. This shows that quality promotional content, promotional design, and promotional media can attract the attention of tourists and increase their interest in visiting these tourist destinations. The relationship of promotions with the needs of tourists is also an important factor to note. Promotions that are relevant to the needs of tourists will be more effective in increasing tourist interest to visit these tourist destinations. The spread of promotions is also an important factor to pay attention to. Promotions that are reached by many people will be more effective in increasing tourist awareness about these tourist destinations. Based on the results of this study, it can be concluded that to improve the effectiveness of tourism promotion in Kwala Serapuh Village, Langkat, efforts need to be made to improve the quality of promotion, the linkage of promotion with tourist needs, and the spread of promotion.